McGraw-Hill Encyclopedia of Science and Technology (Vol.6) : EBE-EYE - McGraw-Hill (New York McGraw-Hill, 2012)
Celebrating more than 50 years of bringing knowledge to readers at all levels of study, the McGraw-Hill Encyclopedia of Science & Technology, 11th Edition provides need-to-know information in the major disciplines of science and technology
Include Table, Graph and Illustration
McGraw-Hill Encyclopedia of Science and Technology (20v.)
Keywords: Science -- Technology